The Effect of Drug Types, Facility, and Infrastructure against the Waiting Times at the Pharmacy Installation of Caruban General Hospital - Farid Amirudin; Koesnadi Koesnadi (Journal for Quality in Public Health, 2021)
Backgorund. Waiting time is one indicator of pharmacy service. The initial study with 5 patients in the pharmacy installation, of Caruban Hospital, concluded that all patients stated that they were tiring and queued for a long time. This study aims to examine whether there is an effect of type of drug, facility, and infrastructure to waiting time to get pharmacy service at Caruban Regional Public Hospital. The Design of this research used quantitative research The sampling technique was purposive sampling with total sample are 100 respondents. The statistical analysis used dummy regression. The average waiting time for pharmacy service is about 60 minutes for concocted drug, Average waiting time for packaged drugs is 46.5 minutes, and mixed drug is 69.5 minutes. 72 respondents stated that the infrastructure was in the good category and the rest said it was moderate.The results of the dummy regression analysis concluded that facilities and infrastructure had a significant effect simultaneously on the waiting time for services. The partial test results showed that the significance value for the facilities and infrastructure variable was 0.000, and for the variable dosage forms in mixed prescriptions it had a significance value of 0.023. The means variable is the variable that most influences the waiting time for the prescription service. The types of drugs in the prescription and waiting room infrastructure have a significant effect simultaneously on the length of queuing for drugs.